Learning English as a second language with artificial intelligence for prospective teachers: a systematic review - Peña-Acuña, Beatriz; Corga Fernandes Durão, Rosana (Frontiers in Education, 2024)
IntroductionArtificial intelligence is revolutionizing English language teaching with personalized assessments and advanced tools, though more studies are needed on its effectiveness and equitable accessibility.MethodA systematic literature review (SLR) was conducted using articles from Web of Science, Scopus, and ERIC to establish theoretical foundations.ResultsAI in learning English as a second language offers personalized tools such as chatbots, pronunciation improvement apps, and platforms that adapt content according to student progress.DiscussionThe study highlights how AI is revolutionizing English learning by personalizing lessons, improving pronunciation, and promoting cultural understanding.